The Current State and Prospects of Economic Development in the EU's EaP Countries - Ilkhom Sharipov; Sergey Lisnyak (CES Working Papers, 2016)
Economic development is one of the main aims of economic policy in many countries around the world. By strengthening the process of economic development, we can bring the state on the path of sustainable growth and ensure stability and security in it. The paper analyzes the main indicators of socio-economic development in the EU's Eastern Partnership countries in the period 2000-2015. It also examines the current state of relations between the Eastern Partnership countries and the European Union. The main purpose of this paper is to determine the current state of affairs and prospects of economic development in the EU's Eastern Partnership Countries.
Keywords: O1; O4; O52; O57; 330; economic development; economic growth; Eastern Partnership